Estudio comparativo de morfología en planta de encina cultivada en distintos envases comerciales - ÁLVAREZ LINAREJOS, L.; RAPP ARRARÁS, I. (II Congreso Forestal Español, 1997)
The aim of the present work is to analize the morfological diferences and its caracterization depending on the container used in nursery production of one year holm oak plants. Six different types of containers -those suitable to be bought in the area were the experiment has taken place- has been used for it. It has been stablished the greatest posible homogeneity in other parameters which influence could have been important such as seeds - which procedence is known-, cultivation media, watering, and microclimate -in greenhouse first and nursery later-. Results for sorne of the factors studied are shown.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español issue: 57 pub-location: Pamplona
Keywords: Containers; Holm oak; Nursery; Plant production

Estudio comparativo de morfología en planta de encina cultivada en distintos envases comerciales - ÁLVAREZ LINAREJOS, L; RAPP ARRARÁS, I (II Congreso Forestal Español, 1997)
The aim of the present work is to analize the morfological diferences and its caracterization depending on the container used in nursery production of one year holm oak plants. Six different types of containers -those suitable to be bought in the area were the experiment has taken place- has been used for it. It has been stablished the greatest posible homogeneity in other parameters which influence could have been important such as seeds - which procedence is known-, cultivation media, watering, and microclimate -in greenhouse first and nursery later-. Results for sorne of the factors studied are shown.
Keywords: Containers; Holm oak; Nursery; Plant production